2020
DOI: 10.1186/s12974-020-01915-0
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Trem2 activation ameliorates amyloid-beta deposition and improves cognition in the 5XFAD model of amyloid deposition

Abstract: Background: Triggering receptor expressed on myeloid cell-2 (TREM2) is a lipid and lipoprotein binding receptor expressed by cells of myeloid origin. Homozygous TREM2 mutations cause early onset progressive presenile dementia while heterozygous, point mutations triple the risk of Alzheimer's disease (AD). Although human genetic findings support the notion that loss of TREM2 function exacerbates neurodegeneration, it is not clear whether activation of TREM2 in a disease state would result in therapeutic benefit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 68 publications
3
70
0
1
Order By: Relevance
“…Single-cell RNA sequencing analysis has revealed that TREM2 is critical for the second step of DAM activation (Keren-Shaul et al, 2017). Overexpression of TREM2 reduced the level of pro-inflammatory cytokines in microglia, whereas TREM2-activating antibody induced significant increases in both pro-inflammatory [IL-1ÎČ, TNF-α, C-C motif chemokine ligand (CCL)2, C-X-C motif chemokine ligand (CXCL)10, Gata3, Rorc] and anti-inflammatory (YM1 and IL1Rn) marker expression in 5 × FAD mice (Long et al, 2019;Price et al, 2020). Thus, TREM2 has complex functions in AD.…”
Section: Triggering Receptor Expressed On Myeloid Cells 2 and Toll-limentioning
confidence: 99%
“…Single-cell RNA sequencing analysis has revealed that TREM2 is critical for the second step of DAM activation (Keren-Shaul et al, 2017). Overexpression of TREM2 reduced the level of pro-inflammatory cytokines in microglia, whereas TREM2-activating antibody induced significant increases in both pro-inflammatory [IL-1ÎČ, TNF-α, C-C motif chemokine ligand (CCL)2, C-X-C motif chemokine ligand (CXCL)10, Gata3, Rorc] and anti-inflammatory (YM1 and IL1Rn) marker expression in 5 × FAD mice (Long et al, 2019;Price et al, 2020). Thus, TREM2 has complex functions in AD.…”
Section: Triggering Receptor Expressed On Myeloid Cells 2 and Toll-limentioning
confidence: 99%
“…Recently, agonistic activity of anti‐TREM2 antibodies have been described (Price et al, 2020; Schlepckow et al, 2020; S. Wang et al, 2020). We developed a mouse monoclonal antibody against human TREM2 using the complete ectodomain of human TREM2 for immunization.…”
Section: Resultsmentioning
confidence: 99%
“…Since the disease‐associated variants studied here cause a partial or almost complete loss‐of‐function, activation of TREM2‐DAP12 signaling could potentially represent a therapeutic approach to normalize regulation of microglial activity (Wes, Sayed, Bard, & Gan, 2016). Indeed, agonistic antibodies have been used to activate TREM2 signaling and even restore some cellular deficits observed in TREM2 R47H expressing cells (Cheng et al, 2018; Price et al, 2020; Schlepckow et al, 2020; S. Wang et al, 2020). The monoclonal anti TREM2 antibody 4B2A3 described here also had agonistic effects on TREM2‐DAP12 signaling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations